Current Status of New Modes of Mechanical Ventilation - Robert M Kacmarek (Canadian Respiratory Journal)
Current approaches to managing patients requiring ventilatory support have focused on a lung protective strategy. This approach limits peak alveolar pressure and tidal volume, and allows hypercapnia. Although hypercapnia is tolerated by many patients, in some the acute acidosis markedly complicates clinical management. Tracheal gas insufflation (TGI) has been designed as an adjunct to conventional ventilation to decrease PaCO2. Although no commercial TGI systems are available, TGI holds great promise and can be expected to be available comercially in the future. Pressure ventilation has become the ventilatory approach of the 1990s, whether pressure support or pressure control. However, problems associated with varying tidal volumes have resulted in manufacturers developing ventilatory modes that combine the beneficial effects of both pressure and volume ventilation.